Portrait of Hindu religious teacher performance certified educator in junior high schools Denpasar - Suarda, I Wayan; Yadnyawati, Ida Ayu Gde; Suda, I Ketut (International Research Journal of Management, IT & Social Sciences, 2018)
This article was intended at discussing not optimal Hindu teacherâs performance who was certified educator in junior high school at Denpasar City. The topic is chosen based on unbalancing between ideal and reality. The government was intended to improve them through certification programs, included improving their welfare. However, the reality was the teacherâs performance who have been certified educator was not optimal. At least, there were three questions discussed i.e., the cause not optimal of their performance, efforts were conducted to improve performance and its implications. The study is used a qualitative approach. Therefore, in terms of the data analysis is not an emphasis on measurement but on the effort to describe and explore.